2021
DOI: 10.1002/cncr.33675
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with newly diagnosed TP53‐mutated acute myeloid leukemia with or without venetoclax‐based therapy

Abstract: Background Venetoclax (VEN) in combination with a hypomethylating agent (HMA) has become the standard of care for patients aged >75 years and for those not eligible for intensive chemotherapy who have newly diagnosed acute myeloid leukemia (AML). The benefit of VEN‐based therapy in patients who have newly diagnosed AML with mutations in the TP53 gene (TP53mut) over standard therapy is undefined. Methods In this single‐institutional, retrospective analysis, the authors assessed the clinical outcomes of 238 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
(95 reference statements)
1
40
1
1
Order By: Relevance
“…The presence of this TP53 lesion is associated with resistance to apoptosis induced by DNA-damaging AML chemotherapy and relatively poor clinical outcomes [ 24 , 25 , 49 ]. Although treatment with hypomethylating agents with or without venetoclax are currently under investigation, none of these agents have overcome therapy resistance conferred by TP53 lesions and improved clinical outcomes [ 50 , 51 ]. A previous report had described MOLM13 cells into which TP53 mutations R175H and R248Q had been introduced along with null alleles [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this TP53 lesion is associated with resistance to apoptosis induced by DNA-damaging AML chemotherapy and relatively poor clinical outcomes [ 24 , 25 , 49 ]. Although treatment with hypomethylating agents with or without venetoclax are currently under investigation, none of these agents have overcome therapy resistance conferred by TP53 lesions and improved clinical outcomes [ 50 , 51 ]. A previous report had described MOLM13 cells into which TP53 mutations R175H and R248Q had been introduced along with null alleles [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several multivariable analyses after adjusting for age, performance status and other relevant disease-and patient-specific factors have demonstrated that even among patients with AML harboring poor-risk cytogenetics, the presence of a TP53 mutation predicts worse OS [8,9]. Similarly, among patients with mTP53-AML, the presence of high-risk cytogenetics like complex or monosomal karyotype have worse OS than patients with non-high risk cytogenetics [16,[25][26][27]. These observations have turned recent attention to TP53 allelic state in AML as patients with mono-allelic loss of TP53 in the pathobiologically similar disease myelodysplastic syndrome may have a prognosis similar to that with wild type TP53; bi-allelic loss of TP53 (predicted by a concurrent TP53 point mutation, deletion or copy neutral loss of heterozygosity) appears to drive the poor prognosis seen with the disease as a whole [28].…”
Section: Associated Factors and Important Considerationsmentioning
confidence: 99%
“…Deciding upon an induction strategy for the younger, intensive therapy appropriate patient may be more nuanced and requires accounting for the presence of concurrent high-risk features like concurrent monosomal/complex karyotype, TP53 VAF or mono-vs. bi-allelic TP53 loss as best predicted by current techniques. The more favorable survival observed for patients with mTP53-AML with TP53 VAF ≤ 40% and without additional high-risk cytogenetic features [16,25,26] may warrant more consideration for intensive induction, perhaps favoring 7 + 3 over CPX-351, for the younger patient with such disease and who is appropriate to receive intensive therapy including alloHCT with myeloablative conditioning.…”
Section: Intensive Vs Less-intensive Inductionmentioning
confidence: 99%
“… 73 A retrospective study involving 238 patients treated with VEN and non-venetoclax-based regimens similarly showed higher response rates, but no difference in OS or RFS with venetoclax-based regimens, regardless of age or intensity of treatment. 74 TP53 mutation was also found to be associated with worse OS in the relapsed/refractory setting in retrospective analyses. 75–77 In vitro studies have supported inactivation of TP53 as a mediator of VEN resistance, as well as other genes that regulate the mitochondrial apoptotic network ( BAX, PMAIP1, TFPD1 ).…”
Section: Introductionmentioning
confidence: 93%